Determinan Struktur Modal Perusahaan Pertambangan Bursa Efek Indonesia tahun 2010-2019 - Michelle Aileen Juanda (Studi Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This research is done to analyze the determinants capital structure determinants of mining companies listed on Indonesian Stock Exchange period 2010-2019. Method: This research used profitability, firm size, liquidity, and assets tangibility as independent variables with capital structure as dependent variable. This research used 2 (two) capital structure which is without lag and with lag. This research divided firm size to small and large category. This research used purposive sampling and panel data analysis with random effect model. Results: Results show that ROA which was used to measure profitability, current ratio to measure liquidity, and assets tangibility has significant impact on mining companies’ capital structure. However, firm size using natural logarithm of sales as measurement does not have significant impact on mining companies’ capital structure. Limitations: This research has limitations by including negative ROA data that can affect the results of the study. This research has limitations in the SIZE category division, where the base year used is only year 2019 and used natural logarithm data from sales. This research only used 1 (one) period and 1 (one) sector in analyzing the determinants of capital structure and does not make comparisons. Contribution: Managers, creditors, and investors can use the results of this research to be taken into consideration in making decisions on corporate funding, borrowing funds, and investing in mining companies.